(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Food security remains as a fundamental problem in most countries along with population increase, purchasing power improvement, and climate change. To support national food security, it is necessary to implement it at the households’ level such as farming on backyard land (pekarangan) areas. This paper aims to review the potencies, policies and programs, as well as constraints related with use of backyard land in supporting food security at households’ level. Backyard land is potential for farming in order to supply family food needs, especially vegetables, to reduce household food expenditure, and to increase the household income. Some constrains are found in backyard farming, such as less intensive cultivation, not a core business, lack of specific technology, and less field workers’ of assistance. Support from various stakeholders is necessary in order to improve backyard farming.